Recent state initiatives: the Governor as policy leader: the Governor as chief administrator - Cheek, Suzan K
Innovative accomplishments of governors are a vehicle for analyzing state governor's performance as policy leaders and as chief executives. Analysis of survey data describing state innovations reveals governors fostering an almost even mix of programs and administrative innovations, reported from agencies where the governor is involved in selection of the agency head. The implications are that governors interested in instituting and institution alizing innovation can do so through their appointments and that the appointive power can be a vehicle for change as well as control program initiatives tended to concentrate in various functional policy areas, such as economic development or education. Management i
Keywords: Management; Bureaucracy; Governors - Powers and Functions